Introducción - Romero Mensaque, Carlos José (Revista de Humanidades, 2016)
Resumen: Presentación del monográfico: Predicación y Religiosidad Popular en la Andalucía de la Modernidad: quinientos años de dominicanismo (1515-2015) Abstract: Presentation of the monograph: Preaching and Popular Religiosity in Andalusiaof Modernity: five hundred years of dominicalism (1515-2015)